Multipath Routing protocol: NCPR and QAMR - Garg, Roopali; Kaur, Guneet (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Mobile ad hoc network is an assembly of mobile nodes with no centralized server. Due to mobility of nodes and decentralized network it is difficult to maintain the quality of service (QoS) in routing the packets from source to destination.Â QoS can be defined in terms of various metrics like delay, bandwidth, packet loss, routing overhead, jitter. Routing can be unicast, multicast or multipath.Â This paper presents the description about the QoS multipath routing algorithm.